Strategi Pengembangan Pariwisata di Tanah Senja dalam Meningkatkan Daya Tarik Wisata di Kabupaten Jombang - Baharudinsyah, Mohammad Vavian; Rachmanu, Edvian Ditya (Jurnal Bisnis Indonesia, 2024)
Jombang Regency has a number of unique tourism potentials, both natural and artificial, one ofwhich is Tanah Senja. This research has the main objective of knowing and analyzing tourismmarketing strategies to increase the attractiveness of Tanah Senja tourism in Jombang Regency. Thisresearch uses a qualitative descriptive method. This research was conducted at Tanah Senja. Thesubjects of this research are owners, employees, and consumers. The data analysis method used inthis research is SWOT analysis. It is hoped that the SWOT analysis will be able to make the directionof future goals to take policies that will benefit the company.Keywords: Marketing Strategy; SWOT Analysis; Tanah Senja